PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP KESETARAAN NILAI SERTA KESETARAAN PERILAKU INVESTASI PADA ANAK KECAMATAN BLAHBATUH - Sayuni, Luh Wahyu Mas; Marhaeni, A. A. I. N. (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Human resources investment is important thing for qualified human resources. This study to analyze 1) Equality of investment behavior in children, 2) Influence of mother's education level, family income, suputra children on equality children's values, 3) Influence mother's education level, family income, suputra children, and equality child values equality investment behavior in children, and 4) Equality in children's values mediating influence mother's educational level, family income, and suputra children equality investment behavior children. Sample used 99 respondents. Analysis techniques using descriptive and path analysis. Mother's education level and family income don’t affect equality of children's values. Suputra children have positive and significant effect equality children's values. Level education of mother, child suputra and equality of children's values have a positive and significant effect on equality of investment behavior children. Family income does not affect the equality of children's investment behavior. Equality of value of children does not mediate the influence of mother's educational level, and family income on equality of investment behavior in children, equality of value of children mediates the influence of suputra children on equality of investment behavior in children. Keywords: Mother's education level, family income, suputra children, equality of children's values, equality of investment behavior in children